A holistic framework with user-centred facilities performance attributes for evaluating higher education buildings. Issue 1 (24th August 2019) - Abisuga, Abiodun Olatunji; Wang, Cynthia Changxin; Sunindijo, Riza Yosia
Abstract : Purpose: This paper aims to identify user-centred facilities performance attributes of higher education buildings and how they can be used to evaluate individual learning spaces. These attributes are then consolidated for developing a post-occupancy evaluation (POE) framework in this context. Design/methodology/approach: A systematic review of the literature on the POE of higher education buildings is conducted. Findings: This study identifies 36 facility performance attributes in higher education buildings, which can be categorised into four dimensions: ambient; spatial; technology; and building support and services requirements. These facility performance attributes need to meet user requirements to achieve satisfactory feedback. It is also important to note that user requirements differ from one learning space to another; thus, it is essential to consider the characteristics of individual learning spaces. Research limitations/implications: The proposed evaluation framework is context-based and may not be suitable to evaluate other types of buildings. It may be further extended and enhanced to meet other facility management evaluation needs. Practical implications: The POE framework developed in this research can be used to generate facilities management analytic to inform future design and improve existing higher education facilities. Originality/value: This research has developed a holistic POE framework tool to meet user requirements in higher education buildings.